RANCANG BANGUN SEPEDA DENGAN PENGGERAK MESIN TYPE MPR-328 AIR COOLED 2 STROKE SINGLE CYLINDER - Wartono ,; Raybian Nur (Program Studi Teknik Otomotif, Politeknik Hasnur, 2019)
Motorbikes are means of transportation that are driven by engines (motors). This type is widely used because the price is relatively cheap. Generally motorbikes use gasoline fuel so the working principle is no different from a motorbike in a car. What is meant by a 4 stroke motorcycle is a motorbike which in each of the two crankshaft turns or four stroke pistons is produced one step or one fuel combustion. The valve is an engine component that functions as a mixture of fuel and air entering the cylinder or as the remaining gas passage combusting out of the cylinder. By changing the timing unit the valve gets various effects on fuel consumption and exhaust emissions. So from the results of the research that has been done showing advancing the timing unit open the valve produces the most economical fuel consumption, namely, 0.0663570 ml / sec and in the exhaust gas CO2 = 0.4%, CO = 0.05%, HC = 65%, O2 = 20.90%. Keywords : design, lawn mower, bicycle